Identifying e-Teachers’ Patterns of Attitude in the Instructor’s Role at the University of Tehran: (A Research Based on Q-Methodology) - fattaneh Taghiyareh; Tayebeh Nikraftar; Zahra Abbasali (Journal of Information Technology Management)
The achievement of eLearning goals is one of the challenges which many universities, including the University of Tehran, are faced with. Since the teacher in electronic and virtual space facilitates and manages learning activities by presenting creative methods, reinforcing these methods is one of the ways to achieve eLearning goals. However, one of the factors which influences on choosing these methods is the perceptions of teachers in this field about their roles. Thus, the goal of the current study is to research different methods of e-Teachers in order to manage teaching-learning process in virtual space. The researcher presumes the effect of teachers' "perception and attitude" about their roles on "teaching and managing method". Therefore, the background related to the research has been studied alongside studying the forum available in this field, and then, a representative sample of these discussions, which indicates teaching methods in the University of Tehran, is selected, and finally, they have been analyzed using Q methodology, and four patterns of attitude were emerged. The researcher names the obtained patterns of attitude: knowledge transmitter, participator, intermediary, and e-Content designer. Among the emerged roles, knowledge transmitter's role is the dominant compared to the other three roles.